Experimental and CFD investigation on temperature distribution of a serpentine tube type photovoltaic/thermal collector. (1st November 2018) - Zhou, Jicheng; Ke, Haoyun; Deng, Xiaoqing
Highlights: Multi-physics model for electrical, thermal based on FEM method is proposed. The model is validated and calibrated on one real experiment study. Simulation research is done on PVT modules from a new perspective of temperature distribution. Temperature distribution is most strongly dependent on tube spacing. Abstract: The issue of temperature distribution is significant in the research of PV/T collectors due to the inherent negative temperature characteristics of solar cells. In this paper, a three-dimensional thermal model of a water-cooled flat-panel PV/T collector with serpentine tube is established using the finite element method, which the simulation accuracy is verified by the experimental data. We investigate the effect of multiple factors on the temperature distribution, including tube spacing, absorber materials, inlet velocity and tube row arrangement, respectively. Our results show that reducing tube spacing is the most effective way to increase uniformity of temperature distribution, and using absorber materials with better thermal properties can improve the temperature distribution partly. However, increasing the fluid inlet velocity has little effect on establishing a uniform temperature field though it can reduce the plate temperature. Temperature is hardly affected by the tube row arrangement, and uniform temperature field cannot be obtained with more bends.